REGULARITIES OF DEGRADATION ARRAY OF LOESS UNDER TECHNO GENESIS - MOKRITSKAYA, T.P. (Institute of Geological Sciences, NAS of Ukraine, 2013)
The article contains results time-series studies of variability properties of the geological environment as a subsystem of natural and industrial systems on the local level is an example of Dnepropetrovsk in the period 1964-2007 years.